Oxidative effects of the pharmaceutical drug paracetamol on the edible clam Ruditapes philippinarum under different salinities - Correia, Bárbara (2022)
Paracetamol, a drug with analgesic and antipyretic properties, is one of the most used substances in human therapeutics, being also frequently detected in aquatic environments. Recent studies report its toxicity towards aquatic species, but the overall amount of data concerning its effects is still scarce. Global changes, likely alterations in abiotic conditions, including salinity, can modulate the interactions of contaminants with biota, conditioning the toxicological responses elicited also by pharmaceuticals. The present article describes the oxidative toxic effects posed by paracetamol on the clam species Ruditapes philippinarum under different salinity conditions. The results demonstrated the establishment of an oxidative-based effect, with significant alteration of several parameters, such as superoxide dismutase (SOD) and the ratio of reduced/oxidized glutathione (GSH/GSSG). Water salinity influenced the response of clams exposed to different paracetamol concentrations, showing the importance of studying physiological traits under realistic test conditions, which are likely to vary in great extent as a result of climate change.